Effects of Stenotic Plaques in Realistic Carotid Artery Aneurysm Models: a CFD Study - Castro, Marcelo Adrian (2014)
Cerebral aneurysms may rarely coexist with a proximal artery stenosis. In that small percent of patients, such coexistence poses a challenge for interventional neuroradiologists and neurosurgeons to make the best treatment decision. According to previous studies, the incidence of cerebral aneurysms in patients with internal carotid artery stenosis is not greater than 5%, where the aneurysm is usually incidentally detected, being 2% for aneurysms and stenoses in the same cerebral circulation. Those cases pose a difficult management decision for the physician. Case reports showed patients who died due to aneurysm rupture months after endarterectomy but before aneurysm clipping, while others did not show any change in the aneurysm after plaque removal, having optimum outcome after aneurysm coiling. The aim of this study is to investigate the intraaneurysmal hemodynamic changes before and after treatment of stenotic plaque. Virtually created moderate stenoses in vascular models of internal carotid artery aneurysm patients were considered in a number of cases reconstructed from three dimensional rotational angiography images. The strategy to create those plaques was based on parameters analyzed in a previous work where idealized models were considered, including relative distance and stenosis grade. Ipsilateral and contralateral plaques were modeled. Wall shear stress and velocity pattern were computed from finite element pulsatile blood flow simulations. The results may suggest that relative angular position may change the wall shear stress within the aneurysm sac.